La Representació dels profetes en la pintura romànica catalana - Pagès i Paretas, Montserrat (Miscel·lània litúrgica catalana, 2010)
This paper deals with the figure of the prophet in the Catalan Romanesque mural and wood painting, its iconography and context, mainly when the prophet sings and proclaims the acomplishment of the prophecies and, more exceptionalley, when he acts as intercessor or when he appears in the synthesis of the visions of Isaiah and Ezequiel.